Mycoplasma pneumoniae triggering the Guillain‐Barré syndrome: A case‐control study. Issue 4 (26th August 2016) - Meyer Sauteur, Patrick M.; Huizinga, Ruth; Tio‐Gillen, Anne P.; Roodbol, Joyce; Hoogenboezem, Theo; Jacobs, Enno; van Rijn, Monique; van der Eijk, Annemiek A.; Vink, Cornelis; de Wit, Marie‐Claire Y.; van Rossum, Annemarie M.C.; Jacobs, Bart C.
Abstract : Objective: Guillain‐Barré syndrome (GBS) is an acute postinfectious immune‐mediated polyneuropathy. Although preceding respiratory tract infections with Mycoplasma pneumoniae have been reported in some cases, the role of M. pneumoniae in the pathogenesis of GBS remains unclear. We here cultured, for the first time, M. pneumoniae from a GBS patient with antibodies against galactocerebroside (GalC), which cross‐reacted with the isolate. This case prompted us to unravel the role of M. pneumoniae in GBS in a case‐control study. Methods: We included 189 adults and 24 children with GBS and compared them to control cohorts for analysis of serum antibodies against M. pneumoniae (n = 479) and GalC (n = 198). Results: Anti– M. pneumoniae immunoglobulin (Ig) M antibodies were detected in GBS patients and healthy controls in 3% and 0% of adults ( p = 0.16) and 21% and 7% of children ( p = 0.03), respectively. Anti‐GalC antibodies (IgM and/or IgG) were found in 4% of adults and 25% of children with GBS ( p = 0.001). Anti‐GalC‐positive patients showed more‐frequent preceding respiratory symptoms, cranial nerve involvement, and a better outcome. Anti‐GalC antibodies correlated with anti– M. pneumoniae antibodies ( p < 0.001) and cross‐reacted with different M. pneumoniae strains. Anti‐GalC IgM antibodies were not only found in GBS patients with M. pneumoniae infection, but also in patients without neurological disease (8% vs 9%; p = 0.87), whereas anti‐GalC IgG was exclusively found in patients with GBS (9% vs 0%; p = 0.006). Interpretation: M. pneumoniae infection is associated with GBS, more frequently in children than adults, and elicits anti‐GalC antibodies, of which specifically anti‐GalC IgG may contribute to the pathogenesis of GBS. Ann Neurol 2016;80:566–580